Locked and loaded: examining Pennsylvanians’ perceptions about arming school personnel and impacts on school safety - Strohacker, Emily R. (Criminal justice studies, 2025)
With proposed legislation that, if enacted, would effectively end Pennsylvania’s gun-free school zones, this study sought to examine the attitudes of Pennsylvanians on arming teachers. Further, this study sought to fill a gap in the literature by examining whether Pennsylvanians perceived schools be safer places to be if teachers were armed. A cross-sectional, online survey was conducted with a sample of 1,039 participants from the Commonwealth of Pennsylvania to gauge opinions on arming teachers. A series of chi-square tests and logistic regressions were computed. Pennsylvanians are split regarding support for arming teachers, with significant differences in opinions observed based on various demographic factors. Notably, the findings indicate that while individuals may support arming teachers, they might not necessarily consider schools safer places to be. Thus, a statewide policy permitting school officials to carry firearms on school property may face significant challenges. Policy implications are discussed.